THE USE OF CHATBOTS IN THE ENGLISH LANGUAGE TEACHING TO PROMOTE MODERN LANGUAGE LEARNING: A LITERATURE REVIEW - Eisenring, Moh. Abraham Akbar; Jamiluddin, Jamiluddin; Hairul, Muh. Arasy; Putri, Dwi (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Our world continues to become increasingly connected. The use of technology has become a must in this modern era to live accordingly. The requirement to use technology also widens the world of teaching, especially in teaching English. Nowadays, all generations of educators, whether young or old generations are expected to utilize technologies in their respective classrooms in an attempt to facilitate students with the newest atmosphere of the teaching and learning process. Speaking of those, chatbots are one of the technologies that can be engaged in English language teaching and learning. Relying on the huge benefit and easiness of implementation, the use of chatbots could be the leading technology for teachers to promote modern language learning. In this literature review-based research paper, the writers would like to encourage the use of chatbots in English language teaching as a medium for teachers to promote modern language learning.